In Vivo Electroporation and Time‐Lapse Imaging of the Rostral Migratory Stream in Developing Rodent Brain. Issue 1 (12th March 2019) - Huang, Zhihui; Wang, Ying
Abstract: Interneurons in the olfactory bulb are generated from neuronal precursor cells migrating from the anterior subventricular zone (SVZa) throughout the embryonic and postnatal life of mammals. This article describes basic methods for in vivo electroporation to label SVZa cells of both embryonic and postnatal rats. In addition, it describes three methods for tracing SVZa progenitors and following their migration pathway and differentiation, including immunohistochemistry, time‐lapse live imaging in slice culture, and time‐lapse imaging following transplantation in slice culture. These methods may be applied to all strains of rats and mice, including reporter mice. They may also be combined with methods such as BrdU labeling, tamoxifen injection, and electrophysiology, allowing one to observe proliferation or control gene expression at specific times and for specific neuronal functions. With time‐lapse live imaging, details of labeled cells can be studied, including morphology, motility pattern, differentiation, and crosstalk between cells. © 2019 by John Wiley & Sons, Inc.